Modulated photoconductivity in the high and low frequency regimes - Schmidt, Javier Alejandro (2008)
Different methods have been proposed to use modulated photoconductivity (MPC) measurements in order to extract information about the density of states (DOS) within the gap of defective semiconductors. Depending on the frequency of the modulation, two regimes have to be considered: the high frequency (HF) and the low frequency (LF) regimes. In this paper, we use computer-generated data, obtained from the complete solution of the MPC equations, to test the different procedures proposed to treat the MPC data in both regimes. We show that Bru¨ggemann’s method provides an accurate reconstruction of the introduced DOS provided the capture coefficients are known, while in the LF limit of Kounavis’ method a factor of two is missing. We also test the accuracy of different procedures proposed to extract the capture coefficients of the defects, which are necessary to get absolute DOS values in the methods that utilize the HF regime. The LF–MPC method, on the other hand, has the advantage that the capture coefficients are not needed.